2014
DOI: 10.1016/j.mam.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Brain tumor stem cells: Molecular characteristics and their impact on therapy

Abstract: Glioblastoma (GBM) is the most prevalent primary brain tumor and ranks among the most lethal of human cancers with conventional therapy offering only palliation. Great strides have been made in understanding brain cancer genetics and modeling these tumors with new targeted therapies being tested but these advances have not translated into substantially improved patient outcomes. Multiple chemotherapeutic agents, including temozolomide, the first-line treatment for glioblastoma, have been developed to kill canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
162
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(175 citation statements)
references
References 246 publications
(350 reference statements)
4
162
1
8
Order By: Relevance
“…As expected, we found that the gene expression variations induced by the combined treatment result from the synergic effects of each conjugate, however, for the specific gene set analyzed, the contribution of the GL21.T-miR137 is clearly predominant over that of the Gint4.T-anti10b conjugate. Indeed, as previously reported, the GSCs share a common characteristic miRNA expression profile [ 42] suggesting that a reduced number of miRNAs act in concert to modulate the expression of large sets of genes that ultimately converge to propagate the stem-cell like glioblastoma cell population. Furthermore, recent reports have highlighted the involvement of miRNA deregulation in maintaining the GSC hypoxic microenvironment [45,46].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…As expected, we found that the gene expression variations induced by the combined treatment result from the synergic effects of each conjugate, however, for the specific gene set analyzed, the contribution of the GL21.T-miR137 is clearly predominant over that of the Gint4.T-anti10b conjugate. Indeed, as previously reported, the GSCs share a common characteristic miRNA expression profile [ 42] suggesting that a reduced number of miRNAs act in concert to modulate the expression of large sets of genes that ultimately converge to propagate the stem-cell like glioblastoma cell population. Furthermore, recent reports have highlighted the involvement of miRNA deregulation in maintaining the GSC hypoxic microenvironment [45,46].…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, several miRNAs are differentially expressed in glioblastoma stem cells and normal neural stem cells and shown to be implicated in maintenance and propagation of the GSCs by regulating malignancy, differentiation and fate determination [42].…”
Section: Discussionmentioning
confidence: 99%
“…Регуляторы взрослого нейрогенеза SOX2 и SOX21 играют ключевую роль в пролиферации неопластических клеток, одновременно их инактива-ция останавливает рост глиомы in vivo [16,29,30].…”
Section: обзорные статьиunclassified
“…TGF-β1-ре цеп-торы локализованы в межклеточных контактах и уси-ливают синтез белков межклеточного матрикса [40]. Под действием секретируемого TGF-β1 ОСК образуют ниши с клетками эндотелия через SDF-1/CXCR4-зависимый путь [21,29], а также дифференцируются в клетки, напоминающие перициты и, обеспечиваю-щие периваскулярную нишу питанием [7].…”
Section: обзорные статьиunclassified
“…Histopathologically, gliomas are classified as astrocytomas, oligodendrogliomas, oligoastrocytomas, and ependymomas [2] . Astrocytomas are the most common and malignant type of glioma, and can be caused by astrocytes, glial progenitors, and cancer stem cells [3][4][5][6] . According to the World Health Organization, gliomas are classified into four grades (I-IV), with glioblastoma (grade IV) being the most common and malignant grade [7] .…”
Section: Introductionmentioning
confidence: 99%